New Records of Trichobranchidae (Annelida: Polychaeta.) From Venezuela - Díaz Díaz, Oscar; Liñero Arana, Ildefonso (Boletín del Centro de Investigaciones Biológicas, 1970)
Forty-four specimens belonging to Trichobranchidae were collected in different substrata from the northeastern coast of Venezuela. Samplings were made in six localities at depths of 0,5-2,0m, employing a corer, with a 14,8cm diameter, to collect the samples on a muddy-sandy floor (Turpialito) with Thalassia testudinum fields on bed bottoms (Toporo, Ensenada de Reyes, Varadero), and squares on rocky substrata floors (Punta Colorada, Cubagua Island and Guacarapo). Trichobranchus glacialis and Terebellides carmenensis were identified; both of which are new records for Venezuelan waters.